2015
DOI: 10.15640/jibf.v3n2a8
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Takaful Awareness among Kuwaitis

Abstract: This research examines the awareness of takaful among Kuwaitis. It endeavours to determine any significant differences and conformities between demographic variables and the four aspects of awareness concerning general information, the features of takaful, shari'ah compliances, and motives of takaful. The research adopted a quantitative research design. Descriptive, T-test, ANOVA, and Discriminant analyses were employed to analyse the data collected via questionnaires. The research sample consisted of a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…It is noted that the results of some of the past studies were contradictory whereby awareness had a negative impact on the acceptance of tak aful, such as in the case of Akhter and Hussain (2012), Ismail et al (2013), Soualhi and al-Shammari (2015), Md Hussein and Ab Rahman (2016b) and Salleh and Laksana (2018). Nonetheless, due to mixed and inconclusive results from past empirical studies, this study develops the following proposition about the expected relationship between Bumiputera contractors' awareness and its influence on their selection of the CAR tak aful product:…”
Section: Ijifmentioning
confidence: 99%
“…It is noted that the results of some of the past studies were contradictory whereby awareness had a negative impact on the acceptance of tak aful, such as in the case of Akhter and Hussain (2012), Ismail et al (2013), Soualhi and al-Shammari (2015), Md Hussein and Ab Rahman (2016b) and Salleh and Laksana (2018). Nonetheless, due to mixed and inconclusive results from past empirical studies, this study develops the following proposition about the expected relationship between Bumiputera contractors' awareness and its influence on their selection of the CAR tak aful product:…”
Section: Ijifmentioning
confidence: 99%
“…Knowledge about Takaful intricacies, operational mechanisms, and its compatibility with Sharia principles contributes to a deeper understanding and perception of the concept (Bhatti & Md Husin, 2020).Studies have shown that individuals possessing comprehensive knowledge of Takaful exhibit a greater inclination towards adopting Takaful arrangements and expressing positive attitudes towards its value proposition (Maiyaki & Ayuba, 2015). (Soualhi & Shammari, 2015),conducted an exploratory study in India to examine the The study also highlighted that although Takaful has considerable potential in Pakistan, its market share remains lower than that of traditional insurance due to a lack of understanding. The authors recommended that Takaful operators focus on raising awareness about Takaful and develop more innovative products to enhance its market presence.…”
Section: Knowledge and Perception Of Takafulmentioning
confidence: 99%
“…The word Takaful comes from the Arabic noun "Kafala," which means "guaranteeing each other," (Rafeea, n.d.). The history of Islamic insurance, according to (Soualhi & Shammari, 2015), began in Mecca and Medina under the "Aquila" system, in which tribes mutually agreed to pay indemnity in the event of a loss to another tribe member.…”
Section: Introductionmentioning
confidence: 99%
“…Variable of intention adapted from (Aziz et al, 2018;Nor & Pearson, 2008;Taylor & Todd, 1995). In addition, four (4) variables which are attitude, awareness, understanding and subjective norm adapted from (Amin, Abdul Rahman, & Abdul Razak, 2013;Aziz et al, 2018;Soualhi & Al Shammari, 2015). Meanwhile variable of religiosity adapted from (Alam, Janor, Zanariah, & Ahsan, 2012;Aziz et al, 2018;Bassir et al, 2014).…”
Section: Sample Procedure and Instrumentsmentioning
confidence: 99%